FRI0138 S100A12 and Calprotectin in Serum and The Aorta of Patients with Cardiovascular Disease and Inflammatory Rheumatic Disease: A Biopsy Study. (15th July 2016) - Tjørve, K.M.C.; Fagerhol, M.; Wang-Fagerland, M.; Mikkelsen, K.; Almdahl, S.M.; Hollan, I.; ,
Abstract : Background: Increased serum calprotectin (s-calprotectin) and S100A12 (s-S100A12) levels are associated with inflammatory rheumatic disease (IRD), and might be involved in the pathogenesis of cardiovascular disease (CVD). Objectives: To compare s-calprotectin and s-S100A12 levels in CVD patients with and without IRD, to IRD patients without CVD, and to healthy controls (HC). Furthermore, to search for relationships between s-calprotectin levels and calprotectin expression in the aortic adventitia. Methods: We examined s-calprotectin and s-S100A12 in patients from the Feiring Heart Biopsy Study: 69 IRD (CVD-IRD group) and 53 non-IRD (CVD group) patients undergoing coronary artery bypass grafting (CABG), 32 IRD patients without any clinical or laboratory sign of CVD (IRD group) and 30 HC. Using immunohistochemistry, we scrutinized biopsies taken during CABG from the aortic adventitia in 19 CVD-IRD and 20 CVD patients for the presence and extent of inflammatory cell infiltrates (ICIs) and calprotectin expression. Results: We found no significant differences in levels of s-S100A12 between the four groups (p=0.56). There was not a significant difference in the calprotectin levels between the CVD-IRD and the IRD (1.30 vs 1.73 mg/l; p=0.16) groups. The groups with CVD (CVD and CVD-IRD) had significantly higher s-calprotectin level than the HC group (1.47 vs. 0.30 mg/l; p<0.0001), and a statistically non-significant trend towards a higher s-S100A12 level (44.12 vs 25.36 mg/l; p=0.13). The groups with IRD (IRD and CVD-IRD) had a significantly higher s-calprotectin level than the CVD (without IRD) group (1.42 vs. 0.25 mg/l; p<0.0001) and the HC group (1.42 vs. 0.29 mg/l; p<0.0001). CVD was not independently related to s-calprotectin (p=0.36) neither in the total population nor in the RA subgroup. Calprotectin expression in the aortic adventitia was significantly related to the presence of inflammatory cell infiltrates (ICI; p=0.05), but not to s-calprotectin levels (p=0.95). Conclusions: s-Calprotectin is independently related to IRD, but not to CVD (neither in the general population nor in RA). Thus, in theory, the previously observed association between s-calprotectin and CVD might be caused by the underlying inflammatory process, e.g. IRD, not by a causal role of calprotectin in the CVD pathogenesis. Disclosure of Interest: None declared